Experimental study of the operation of a Stirling engine with a solar concentrator and an additional energy source - Golovko , V.; Berezhniuk, M. (Energy and Automation, 2025)
The efficiency of solar energy is limited by the natural variability of solar radiation levels. The Stirling engine is a promising solution for solar energy systems, especially when using concentrators, such as a Fresnel lens. The main obstacle to the widespread implementation of such systems is their dependence on the stability of solar radiation.The purpose of the research is to create an experimental stand and methodology to determine the feasibility of using an additional energy source (electric heater) to prevent the shutdown of the Stirling engine, which uses concentrated solar radiation using a Fresnel lens as the main source of heat.The paper presents an experimental study of the Stirling engine, which includes the study of the effect of variable insolation and the assessment of the efficiency of using an electric heater as an additional energy source (AES) to improve system stability. A series of experiments was conducted with different durations of insolation interruption (20, 40 and 60 s). The results confirmed the ability of the AES to prevent engine shutdown and increase the total energy produced by 47 %, 90 % and 130 % for the respective intervals.Key words: Stirling engine, Fresnel lens, additional energy source, power stabilization, solar energy, experimental stand